EFEKTIVITAS METODE COLLABORATIVE LEARNING DALAM MEMBEDAH KONSEP RETHINKING GOVERNMENT DI ERA DIGITAL - Djasuli, Mohammad; Ismiyanti; Irawati, Awwaliya putri; Nahidoh, Nidaul syofiyun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The complexity of the concept of Rethinking Government in the digital era demands learning methods that are not only theoretical, but also applicable and participatory. This study aims to analyze the effectiveness of the Collaborative Learning method in dissecting the concept of contemporary governance at the higher education level. The method used is qualitative descriptive with a narrative review approach to various current scientific publications on digital pedagogy and public policy. The results of the study show that the implementation of Collaborative Learning significantly increases students' critical understanding of bureaucratic digitalization and public sector innovation. Interaction between students in solving case studies related to e-government triggers higher-order thinking skills. The use of digital collaboration platforms such as Google Classroom and Padlet has proven to be a catalyst in accelerating the distribution of knowledge in an inclusive manner. This study concludes that collaborative methods are effective in transforming abstract concepts of Rethinking Government into practical understandings that are relevant to the needs of industries in the digital era. The success of this method is highly dependent on the role of lecturers as facilitators and the availability of adequate technological infrastructure. Keywords: Collaborative Learning, Rethinking Government, Digital Era, Learning Effectiveness, Educational Innovation